Catalyst screening for CO2 oxidative coupling of methane to C2 hydrocarbons - Istadi, Istadi; Saidina Amin, Nor Aishah (Universiti Malaysia Sabah, 2003)
Basic metal oxides are suitable catalysts for the selective oxidative coupling of methane reaction using CO2 as an oxidant known as CO2 OCM hereafter. Catalysts screening for CO2 OCM was performed using CeO2- and MgO-based catalysts. The performance of the catalysts was tested in a fixed-bed quartz reactor. The CeO2 support was combined with alkaline earth metal oxide (CaO) and transition metal oxide (WO3 or MnO) to form a ternary metal oxide catalyst. The other catalyst tested was MgO doped with Li2O. The addition of WO3 to the CeO2 catalyst is able to enhance the C2 hydrocarbon selectivity, while the addition of MnO doping was able to increase the C2 hydrocarbons yield and CH4 conversion. The Li2O/MgO catalyst is a more promising catalyst for CO2OCM rather than CeO2-based catalysts. The C2 hydrocarbon yield of 5.7% and selectivity of 92.7% were obtained over Li2O/MgO catalyst. Raman spectroscopy was employed to characterize the catalysts.